Studies on Morphological Variability among Wild Ganoderma lucidum (W. Curt: Fr.) P. Karst - Thakur, Renu; Kapoor, Pooja; Sharma, B. M.; Kumar, Ashok (Indian Forester, 2018)
Morphological characteristics of 23 fruit bodies of Ganoderma lucidum were investigated to understand the effect of environment on the growth and development of its basidiocarp. These studies are important because medicinal value of G. lucidum lies in its basidiocarp and fruiting bodies growing in wild were found to have more active ingredients. Various fruitbodies were collected from different geographical areas of Himachal Pradesh (representing different climatic conditions) on wide variety of dead, dying and living trees. Morphology and variability of the sporophores was studied with reference to shape, size and colour.